THE INFLUENCE OF GREEN STRATEGY AND INTERNATIONAL OPERATIONS ON CARBON EMISSION DISCLOSURE WITH OWNERSHIP CONCENTRATION AS A MODERATION VARIABLE - Juna Sari Berutu; Holiawati; Nofryanti (ZILLZELL MEDIA PRIMA, 2025)
This study investigates the effect of Green Strategy and International Operation on Carbon Emission Disclosure (CED), with a specific focus on the moderating role of Ownership Concentration. Using a quantitative associative approach and panel regression analysis, data were collected from 72 financial sector companies listed on the Indonesia Stock Exchange (IDX) over the period 2020–2023, resulting in 288 firm-year observations. The study employs a panel data regression model and Moderated Regression Analysis (MRA) to test the proposed hypotheses. The results reveal that both Green Strategy and International Operation have a significant positive effect on Carbon Emission Disclosure, confirming that environmentally oriented strategies and international business exposure lead to greater transparency in emission reporting. Moreover, Ownership Concentration does not moderate the relationship between Green Strategy and Carbon Emission Disclosure. However, it positively moderates the relationship between International Operation and Carbon Emission Disclosure, suggesting that highly concentrated ownership enhances the strategic influence of international exposure on environmental reporting. This study contributes to the growing body of literature on corporate environmental disclosure by providing empirical evidence from an emerging market context. The findings support the Stakeholder Theory and Legitimacy Theory, indicating that both internal corporate strategies and external operational contexts play vital roles in shaping environmental transparency.